Advocatus populi i advocatus diaboli – o prawie, argumentach i strategiach stron negocjujących Brexit - Arkadiusz Radwan (Ksiegarnia Akademicka Publishing, 2021)
Advocatus populi and advocatus diaboli – on law, arguments and strategies in Brexit negotiations